Urban Growth, Liveability and Quality Urban Design: Questions about the efficacy of urban planning systems in Auckland, New Zealand - Lee Beattie; Errol Haarhoff (Alanya Hamdullah Emin Paşa Üniversitesi, 2018)
Preventing sprawl and concentrating future urban growth at transit centres, typifies many urban planning strategies in a number of Australian, New Zealand and North America cities. Newer iterations of these strategies also argue that compact development delivers public benefits by enhancing urban ‘liveability’ through good urban design outcomes. Where neoliberal economic conditions prevail, achieving these aims is largely dependent on market-driven development actions requiring the appropriate urban planning responses to ensure these outcomes. However, there are growing concerns that urban planning approaches currently used are not effectively delivering the quality urban design outcomes expected and enhancing residents’ liveability. This paper reports on an evaluation of three medium density housing developments located in areas designated for intensification in Auckland, New Zealand. Examined is the extent to which the development outcomes are aligned with the statutory urban planning requirements for quality urban design. The results indicated contradictions and points to limitations of the statutory planning system to positively influence quality outcomes, leading to enhanced residents’ experiences.